Ecosystem services of urban agriculture and prospects for scaling up production: A study of Detroit. (June 2022) - Newell, Joshua P.; Foster, Alec; Borgman, Mariel; Meerow, Sara
Abstract: Urban agriculture provides a range of ecosystem services (as well as potential disservices). This study examines the spatial extent, physical characteristics, and residents' perceptions of community and private gardens in Detroit, a city that has high potential for agricultural development given its abundant vacant and abandoned land. Despite popular narratives of Detroit as a mecca for urban agriculture, spatial analysis of the city's Lower Eastside ( 15 sq. miles) reveals that gardens cover less than 1% of the vacant land and are often an ephemeral form of land use. Interviews indicate that residents plant gardens primarily for the cultural ecosystem services (e.g. social cohesion, community building) they provide and secondarily for provisioning services (i.e. food production). Uncertainty over land tenure, legacy environmental pollutants, unknowns regarding potential ecosystem disservices, and lack of government support and capital investment are the primary obstacles to scaling up urban agriculture in Detroit and other cities and will need to be addressed. To facilitate its expansion, we propose that urban agriculture be framed as a form of multifunctional green infrastructure. We conducted GIS-based analysis to identify suitable parcels for scaling up agriculture in the study area. To maximize the distribution of ecosystem service benefits, our modeling recommends dispersing rather than clustering gardens in the urban landscape. This strategy would provide more benefits to more people while countering the gentrification effects that may occur when cities expand green space. Highlights: Urban agriculture provides a range of ecosystem services (and disservices). Less than 1% of the vacant land in Detroit's Lower Eastside is being used for urban agriculture. Residents plant gardens primarily for their cultural ecosystem services. Land tenure issues, legacy pollutants, and government support are obstacles. Gardens should be dispersed rather than clustered to maximize urban ecosystem services.